President's Message: Networking... Present and Future - Hill, Marlene (Operating Room Nurses Association of Canada Journal, 2000)
For many years our American colleagues have hosted yearly conferences for Operating Room Nurse Managers and frequently our leaders would travel to these sessions because there was nothing equivalent available in Canada.